FRI0074 Status of Disease Activity, Functional Impairment and Treatment in Patients with Rheumatoid Arthritis and Comorbidities. (9th June 2015) - Tanaka, E.; Inoue, E.; Yamaguchi, R.; Shimizu, Y.; Sugimoto, N.; Hoshi, D.; Shidara, K.; Sato, E.; Seto, Y.; Nakajima, A.; Momohara, S.; Taniguchi, A.; et al.
Abstract : Background: Rheumatoid arthritis (RA) reduces functional ability and quality of life. Comorbidities may have considerable impact on physical function, and functional disability consistently increases with higher levels of comorbidity, irrespective of RA disease activity (1). We reported that patients with many comorbidities were treated less frequently with methotrexate (MTX) and biologics and tended to exhibit corticosteroid dependency, resulting in worse physical function (2); however, the effects of different comorbidities on treatment strategy and subsequent outcomes, such as disease activity and physical function, have not been evaluated. Objectives: To assess disease activity, functional impairment and treatment in Japanese RA patients with comorbidities in daily practice. Methods: Among the patients who participated in the Institute of Rheumatology, Rheumatoid Arthritis (IORRA) study in October 2013, we extracted those who answered "yes" to the question, "Have you ever had or do you currently have any of the following diseases?", and cross-sectionally assessed patient characteristics, disease activity, functional impairment and treatment by comorbidity: (1) angina pectoris/myocardial infarction (coronary artery disease [CAD]), (2) cerebral hemorrhage/cerebral infarction/subarachnoid hemorrhage (stroke), (3) hypertension, (4) heart failure, (5) interstitial pneumonia (IP), (6) pulmonary emphysema/chronic bronchitis/asthma/bronchiectasis (chronic obstructive pulmonary disease [COPD]), (7) gastric ulcer/duodenal ulcer/gastrointestinal hemorrhage (GI), (8) hepatic dysfunction/viral hepatitis, (9) cancer, (10) depression, (11) diabetes, (12) fracture. Results: The study included 5, 837 patients with RA (mean age, 60.9 y; RA duration, 14.8 y; females, 85.5%; DAS28, 2.6; Japanese version of the HAQ [J-HAQ] score, 0.59; percentage of patients receiving MTX/corticosteroid/biologics, 77.4%/33.2%/18.8%). The most common comorbidity was hypertension (19.3%), followed by COPD (4.7%), GI (4.5%), diabetes (4.4%), fracture (4.0%) and IP (2.8%). The mean age was highest in patients with CAD (71.6 y) and lowest in those with depression (58.1 y). The mean DAS28 was below 3.0, except in patients with IP (3.2) and cancer (3.0), whereas all comorbidities except hypertension and diabetes (0.78) had a J-HAQ score of 0.8 or more; in particular, fracture (1.04) and IP (1.01) were associated with more advanced functional impairment. The percentage of patients receiving MTX was lowest for IP (47.6%) and heart failure (55.3%) and highest for depression (77.3%). The percentage of patients receiving corticosteroids was highest for IP (68.1%) and lowest for diabetes (36.3%). The percentage of patients receiving biologics was highest for IP (25.9%) and depression (21.8%), and lowest for cancer (12.5%). Conclusions: Although the choice of RA therapy varies among different comorbidities, current RA therapy provides adequate control to achieve low disease activity or remission in most patients. However, progression of functional impairment cannot be avoided in the presence of comorbidities, suggesting the importance of prevention and treatment of comorbidities, in addition to the control of RA disease activity. References: Radner H. Ann Rheum Dis 2010. Nakajima A. Clin Rheumatol 2014. Disclosure of Interest: E. Tanaka: None declared, E. Inoue: None declared, R. Yamaguchi: None declared, Y. Shimizu: None declared, N. Sugimoto: None declared, D. Hoshi: None declared, K. Shidara: None declared, E. Sato: None declared, Y. Seto: None declared, A. Nakajima: None declared, S. Momohara Consultant for: AbbVie, Bristol-Myers-Squibb, Eisai, Mitsubishi-Tanabe, and Takeda., A. Taniguchi Grant/research support from: Takeda., Consultant for: AbbVie, Eisai, Mitsubishi-Tanabe, and Teijin., H. Yamanaka Grant/research support from: AbbVie, Asahikasei Pharma, Astellas, Bristol-Myers-Squibb, Chugai, Daiichi-Sankyo, Eisai, GlaxoSmithKline, Janssen, Mitsubishi-Tanabe, MSD, Nippon Kayaku, Pfizer, Santen, Taisho-Toyama, Takeda, and Teijin Pharma., Consultant for: Teijin Pharma, Chugai, Astellas, Bristol-Meyers, AbbVie, Daiichi-Sankyo, Nihon-Kayaku, Mitsubishi-Tanabe, Pfizer, Takeda, and UCB.